2013
DOI: 10.1007/s10964-013-0052-0
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhoods and Racial/Ethnic Disparities in Adolescent Sexual Risk Behavior

Abstract: Understanding the determinants of racial/ethnic disparities in adolescent sexual risk behavior is important given its links to the differential risk of teen pregnancy, childbearing, and sexually transmitted infections. This article tests a contextual model that emphasizes the concentration of neighborhood disadvantage in shaping racial/ethnic disparities in sexual risk behavior. We focus on two risk behaviors that are prevalent among Black and Hispanic youth: the initiation of sexual activity in adolescence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 54 publications
3
48
0
Order By: Relevance
“…36,37 In our study, higher levels of observed violence in the environment increased the odds of a pregnancy among females in Johannesburg and males in Baltimore. This is consistent with how neighbourhoods with higher levels of violence, crime and poverty have been shown to increase adolescent sexual risk behaviours.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…36,37 In our study, higher levels of observed violence in the environment increased the odds of a pregnancy among females in Johannesburg and males in Baltimore. This is consistent with how neighbourhoods with higher levels of violence, crime and poverty have been shown to increase adolescent sexual risk behaviours.…”
Section: Discussionsupporting
confidence: 44%
“…This is consistent with how neighbourhoods with higher levels of violence, crime and poverty have been shown to increase adolescent sexual risk behaviours. 36,38 Both Johannesburg and Baltimore are characterized by housing instability, densely populated neighbourhoods, abandoned buildings occupied illegally, unclean neighbourhoods, and few green and recreational spaces for adolescents. In the qualitative study 14 the piling up of trash, inadequate and crowded housing, lack of basic services such as water and electricity were major health concerns among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…A main focus of this neighborhood-level research has been to understand how neighborhood socioeconomic (SES) disadvantage is associated with sexual health. Living in a socioeconomically disadvantaged neighborhood is associated with a greater likelihood of sexual debut among adolescents (Carlson, McNulty, Bellair, & Watts, 2014; Cubbin, Santelli, Brindis, & Braveman, 2005; Voisin, Hotton, & Neilands, 2014), a greater number of sexual partners (Carlson et al, 2014), and a higher likelihood of being infected with an STI (Ford & Browning, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…First, much of the research in this area has been conducted with adolescents (e.g., Brady, 2006; Brahmbhatt et al, 2014; Kerr, Valois, Siddiqi, Vanable, & Carey, 2015; Voisin, 2005; Wilson et al, 2012); there is limited research on the relation between community violence and sexual risk behavior among adults. Second, although SES, at the individual level and at the community level, is a correlate of both sexual risk behavior (Carlson et al, 2014; Cubbin et al, 2005; Ford & Browning, 2014; Voisin et al, 2014) and community violence (Ewart & Suchday, 2002; Morenoff, Sampson, & Raudenbush, 2001), research on community violence has rarely controlled for SES.…”
Section: Introductionmentioning
confidence: 99%
“…The authors thoughtfully address three highly influential domains of family, neighborhood, and schools in which developmental traumas and triumphs can affect the likelihood of later adolescent violent behavior. In this regard, they contribute to a growing literature that examines the multiple ways that economic forces influence youth's developmental outcomes, such as their risk taking (Carlson et al 2014) and alcohol use (Hardaway and Cornelius 2014) as well as physical and mental health (Brenner et al 2012;Lee et al 2013). But, unlike a large majority of developmental research in this area, the authors maintain a sense of realism with the reader admitting that some economic inequity is likely inevitable and, thus, some observed effects on adolescence are unavoidable.…”
mentioning
confidence: 99%